Neutralising rivaroxaban induced interference in laboratory testing for lupus anticoagulant (LA): A comparative study using DOAC Stop and andexanet alfa. Issue 180 (August 2019) - Favaloro, Emmanuel J.; Gilmore, Grace; Arunachalam, Sandya; Mohammed, Soma; Baker, Ross
Abstract: Introduction: Lupus anticoagulant (LA) investigation in patients on anticoagulant therapy is problematic. Rivaroxaban in particular causes significant interference, prolonging both LA screening and confirmation tests, and falsely raising LA screen/confirm ratios, leading to potential false identification of LA. The Russell Viper Venom Time (RVVT) assay, key to the investigation of LA, is especially sensitive to rivaroxaban. Materials and methods: We assessed cross laboratory (n = 82) testing of four samples to investigate whether rivaroxaban induced interference in LA testing could be neutralised. Testing was performed blind to sample type. The samples comprised: (A) A pool of normal plasma (LA-negative control); (B) sample A spiked with rivaroxaban (200 ng/mL) to create rivaroxaban-induced interference (LA 'false' positive sample); (C) sample B subsequently treated with a commercial 'DOAC-neutraliser' (DOAC Stop); (D) sample B treated with andexanet alfa (200 μg/mL). Results: As expected, the rivaroxaban-spiked sample (B) caused prolongation of most LA-tests, and also generated a falsely prolonged RVVT screen/confirm ratio (median 1.37, compared to 0.97 for sample A). The sample (C) treated with DOAC Stop evidenced a correction in LA-test clotting times, as well as neutralising the false positive LA (median RVVT screen/confirm ratio of 0.99). Although the andexanet alfa treated sample (D) also yielded a low median RVVT screen/confirm ratio of 0.88, it did not fully correct LA-test clotting times. Consistent with test findings, all laboratories interpreted samples A and C as being LA-negative. For sample B (rivaroxaban), 45.3% identified this as LA positive, and 38.7% identified LA interference. Most (61.3%) also identified sample D as LA negative, with the remainder (38.7%) identifying LA interference. Conclusions: DOAC Stop was able to neutralise the false LA activity induced by rivaroxaban, both in terms of clot-times and LA ratios. In contrast, whilst andexanet alfa negated the rivaroxaban-prolonged LA-ratio, it did not fully correct clot-times, leaving some residual LA interference, and requiring additional testing to investigate prolonged clotting times. Highlights: DOACs, especially rivaroxaban, interfere with LA testing and can generate false positive LA. DOAC Stop can neutralise DOAC interference, and nullify rivaroxaban induced false positive LA. Andexanet only partially neutralises the rivaroxaban induced false positive LA. This is the first such evaluation in a cross-laboratory (n = 82) exercise.